Hospice Philosophy in Practice—Toward an Authentic Death. (June 2021) - Graven, Vibeke; Timm, Helle
This article examines how hospice philosophy works in contemporary Danish hospice practice. The still sparse literature on Danish hospices indicates that hospice philosophy is influencing professional practice. In international palliative care literature, hospice philosophy is challenged for being overly normative in its ideal of the good death or on the other hand as threatened by the medical model. Drawing on the idea of hospice philosophy as providing meaning for everyday practice, this article explores how it is incorporated within the institutional order of contemporary Danish hospices. An ethnographic study was informed by participant observation and 49 interviews with professionals, patients, and families at three hospices in Denmark. The findings contribute to further understanding of the complexity of maintaining hospice philosophy in contemporary practice. Hospice practice works in an interpretive way with hospice philosophy to offer a "lived" philosophy and a means to an authentic death.